A novel mutation in ryanodine receptor 2 (RYR2) genes at c.12670G>T associated with focal epilepsy in a 3-year-old child - Hu, Junji; Gao, Xueping; Chen, Longchang; Zhou, Tianshu; Du, Zhaoli; Jiang, Jinghan; Wei, Lei; Zhang, Zhijun (Frontiers in Pediatrics, 2022)
Background: Ryanodine receptor 2 (RYR2) encodes a component of a calcium channel. RYR2 variants were well-reported to be associated with catecholaminergic polymorphic ventricular tachycardia (CPVT), but rarely reported in epilepsy cases. Here, we present a novel heterozygous mutation of RYR2 in a child with focal epilepsy. Methods: At the age of 2 years and 7 months, the patient experienced seizures, such as eye closure, tooth clenching, clonic jerking and hemifacial spasm, as well as abnormal electroencephalogram (EEG). Then, he was analyzed by whole-exome sequencing (WES). The mutations of both the proband and his parents were further confirmed by Sanger sequencing. The pathogenicity of the variant was further assessed by population-based variant frequency screening, evolutionary conservation comparison, and American Association for Medical Genetics and Genomics (ACMG) scoring. Results: WES sequencing revealed a novel heterozygous truncating mutation (c.12670G>T, p.(Glu4224*), NM_001035.3) in RYR2 gene of the proband. Sanger sequencing confirmed that this mutation was inherited from his mother. This novel variant was predicted to be damaging by different bioinformatics methods. Cardiac investigation showed that the proband had no structural abnormalities, but sinus tachycardia. Conclusion: We proposed that RYR2 is a potential candidate gene for focal epilepsy, and epilepsy patients carried with RYR2 variants should be given more attention, even if they do not show cardiac abnormalities